Evaluation of space comfort based on occupant satisfaction in west Jatinegara flats residential units - Ulinata; Sally Septania Napitupulu; Adinda Garda Merah; Kristoforus Dandy (ARTEKS : Jurnal Teknik Arsitektur, 2023)
The Special Capital Region (DKI) of Jakarta is an area that experiences population growth every year, which raises the number of housing-related needs and reduces the amount of available vacant land for housing. In order to get around the lack of land for housing, a plan for flats—like the West Jatinegara Flats—must be implemented. The spaces in an apartment that are designed by an architect are required to produce a design that takes into account the comfort factor of the space for the occupants or users in addition to aesthetics. Residents feel comfortable if they are at a thermal temperature of between 22.8℃-25.8℃ with humidity of 70%. The study, "Evaluation of Space Comfort based on Occupant Satisfaction in West Jatinegara Flats Residential Units," attempts to ascertain whether or not improving strategies are required to raise space comfort based on occupant satisfaction and whether or not an appropriate level of space comfort is achieved. This study employs the quantitative method, which entails gathering primary and secondary data and conducting interviews with at least 10% of the resident population selected at random. This study's results indicate that improvement strategies are required to improve room comfort. These strategies include organizing each room to make it cozier and more compact, considering the type of opening material, the opening area ratio, and the materials used for the glass and frame to prevent breakage and damage to the windows and handles. Every room in the residential unit needs to have optimal air exchange during strong wind conditions.